2019
DOI: 10.1155/2019/3526407
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Competing Endogenous RNA Network Identifies Novel mRNA, miRNA, and lncRNA Markers in Human Cholangiocarcinoma

Abstract: Background. Cholangiocarcinoma (CCA) is the second most common malignant primary liver tumor and has shown an alarming increase in incidence over the last two decades. However, the mechanisms behind tumorigenesis and progression remain insufficient. The present study aimed to uncover the underlying regulatory mechanism on CCA and find novel biomarkers for the disease prognosis. Method. The RNA-sequencing (RNA-seq) datasets of lncRNAs, miRNAs, and mRNAs in CCA as well as relevant clinical information were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The upregulation of MST1R promotes the progression of many epithelial cancers, including pancreatic, lung, and breast cancer [4648]. We previously demonstrated that MST1R is upregulated and associated with overall survival in CCA [49]. However, the underlying mechanisms regulating MST1R remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of MST1R promotes the progression of many epithelial cancers, including pancreatic, lung, and breast cancer [4648]. We previously demonstrated that MST1R is upregulated and associated with overall survival in CCA [49]. However, the underlying mechanisms regulating MST1R remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…COL18A1 Antisense RNA 1 (COL18A1-AS1), is a lncRNA located in 21q22.3. Some bioinformatics analysis has reported that COL18A1-AS1 could be a biomarker for Cholangiocarcinoma [ 23 , 24 ] and RCC [ 25 , 26 ]. Gene Set Enrichment Analysis (GSEA) showed that COL18A1-AS1 might participated in lipid metabolism signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular chemical signals released from these pseudo-synapses are a likely cause of breast cancer brain metastasis [42][43][44][45]. An analysis of the TCGA database has also implicated GRID2IP as a novel prognostic marker in patients with cholangiocarcinoma [46]. TMEM117 is a six transmembrane protein with a conserved sequence; it is present in pro-and anti-apoptotic BCL-2 family of proteins.…”
Section: Discussionmentioning
confidence: 99%